Recovering the full mission of God : a Biblical perspective on being, doing, and telling - Flemming, Dean E., 1953- (Downers Grove, Illinois : IVP Academic, An imprint of InterVarsity Press, 2013)
Is our gospel witness too small? Should the gospel be proclaimed in words only? Or should we preach the gospel in deeds -- and when necessary use words? Or are we missing something in playing the witness of words against deeds? If you are concerned about evangelizing the post-Christian West or the world beyond, you have probably debated this issue. And evangelical instincts drive us to Scripture. In Recovering the Full Mission of God, Dean Flemming joins biblical scholarship with missionary experience as he surveys the Old Testament and then looks closely at the New Testament and the early church. Flemming shows how the three strands of telling, doing and being relate in the mission of God and his people. Here is a book in touch with the missional realities of our time and grounded in the missional vision of biblical revelation. It gives us a clear vision of the rich and multifaceted nature of "gospeling" the kingdom of God. - Publisher.
Introduction -- A people of blessing : Israel's missional life -- A story to tell to the nations? : Israel's witness of the word -- Announcing and embodying God's reign : the full mission of Jesus -- Doer, teacher, Savior : portraits of mission in the Synoptic Gospels -- A mission of sending love : being, doing and telling in John's Gospel -- You will be my witnesses : speaking and living the gospel in Acts -- Compelled by Christ's love : Paul's holistic mission -- Partners in the gospel : the missional life of Paul's churches -- Mission from the margins : being, doing and telling in 1 Peter -- Following the Lamb : word and life mission in Revelation -- What difference does it make? : Concluding reflections -- For further reading.
Includes bibliographical references (pages 278-279) and indexes.
Keywords: Evangelistic work -- Biblical teaching; Missions -- Theory -- Biblical teaching; Missional church movement; Evangelistic work -- Biblical teaching; Missions -- Theory -- Biblical teaching